Public Finance and Public Policy - Gruber Jonathan (Worth Publishers, 2007)
When first published, Gruber's Public Finance and Public Policy brought a refreshingly contemporary approach. It was the first text written from the ground up to reflect current realities of public finance, enhancing its survey of traditional topics with an emphasis on empirical work and coverage of transfer programs and social insurance. The new edition, fully updated with the most recent data and research possible, includes new coverage of the Medicare drug benefit, changes in the tax code, Hurricane Katrina, and the ongoing debate over privatization.